Determinant Model of Student Entrepreneurship Awareness - Hendrajaya, Hendrajaya; Widodo, Joko; Rachman, Maman; Raharjo, Tri Joko (The Journal of Educational Development, 2019)
This study aimed to analyze factors that influence the awareness in student entrepreneurship. The research took the form of a survey of 140 final-year students at the Indonesia Tourism Economics College (STIEPARI) Semarang who were or had taken an internship program. The benefits of Mobile Learning were measured by students' perceptions in gaining knowledge, experience, and social motivation about entrepreneurship. Data were analyzed using Structural Equation Modeling (SEM). The results of this study generally show that in entrepreneurship education through an apprenticeship program, the perception about the benefits of M-Learning and that of entrepreneurship feasibility have a significant effect on the interest in entrepreneurship both directly and through perception of entrepreneurial desires. The total influence of entrepreneurship education variables through the apprenticeship program shows that the path coefficient is greater than the perception variable on benefits so that M-Learning only functions as a support for entrepreneurship education in an internship program to increase students' entrepreneurial interest. The results of this study have implications for the development of electronic learning through M-Learning to support entrepreneurial learning. M-Learning, for example, has the potential to provide independent learning, opportunities for sharing knowledge, problem solving-based experiences, and entrepreneurial motivational facilities, solving the problem of busy time mentors in the industrial environment, and learning that is not limited to space and time.